Properties of coating systems during the initial period of deep-fat frying as affected by flour type, temperature and pressure - Salma Mohamad Yusop; Mohamad Yusof Maskat; Wan Aida Wan Mustapha; Aminah Abdullah (Universiti Kebangsaan Malaysia, 2009)
This study was carried out to determine the properties of coatings made from wheat, rice and sago flour when fried under different frying temperature and pressure during the initial period of deep-fat frying. Three types of batter made from wheat, rice and sago flour were prepared by mixing each flour with water at a ratio of 1:1.2 (flour: water). Poultry nuggets were dipped in the prepared batter and fried for 0, 6, 18 and 30 seconds at three frying temperatures (150, 165, 180°C) and two frying pressures (102 and 156 kPa). Results showed that the frying pressure applied did not produce any significant effect on moisture content, normalized moisture loss and fat content up to 30 seconds of frying. All parameters except moisture content of the coating region were significantly (p<0.05) affected by flour type. Coating from sago flour produced the highest normalized moisture loss and fat content compared to other flour.